NLRP3+ macrophages aggravate inflammatory cystitis in diabetes - Peng, Yubing; Gao, Yan (Frontiers in Immunology, 2022)
Inflammatory macrophages play a pivotal role in the progression of inflammatory cystitis. Formation of NOD-, LRR- and PYD domains-containing protein 3 (NLRP3) inflammasome triggers the activation of caspase-1/IL-1β signaling cascades to mediate inflammatory response. However, it is not known whether NLRP3 activation in macrophages during cystitis may differ in normal or diabetic setting as well as the importance of it. In this study, we found that NLRP3 levels significantly increased in bladder macrophages in diabetic mice that underwent cystitis. Moreover, bladder macrophages from diabetic mice appeared to have increased their potential of growth, migration and phagocytosis. Furthermore, specific depletion of NLRP3 in macrophages alleviated the severity of cystitis in diabetic mice, but not in non-diabetic mice. Together, our data suggest that NLRP3 depletion in macrophages may be a promising strategy for treating diabetic cystitis.